2011
DOI: 10.1152/physiolgenomics.00032.2010
|View full text |Cite
|
Sign up to set email alerts
|

SERCA2a superinhibition by human phospholamban triggers electrical and structural remodeling in mouse hearts

Abstract: Phospholamban (PLN), the reversible inhibitor of the sarco(endo)plasmic reticulum Ca(2+)-ATPase (SERCA2a), is a key regulator of myocyte Ca(2+) cycling with a significant role in heart failure. We previously showed that the single amino acid difference between human and mouse PLN results in increased inhibition of Ca(2+) cycling and cardiac remodeling and attenuated stress responses in transgenic mice expressing the human PLN (hPLN) in the null background. Here we dissect the molecular and electrophysiological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 45 publications
(44 reference statements)
0
12
0
Order By: Relevance
“…Both null and missense mutations in the human phospholamban gene cause cardiomyopathy, heart failure, cardiomyocyte enlargement, decreased contractile function, and electrophysiological remodeling (28, 39, 40). PLN has been described in the murine gastric smooth muscle as well as in the airway of beta receptor overexpressing mice.…”
Section: Discussionmentioning
confidence: 99%
“…Both null and missense mutations in the human phospholamban gene cause cardiomyopathy, heart failure, cardiomyocyte enlargement, decreased contractile function, and electrophysiological remodeling (28, 39, 40). PLN has been described in the murine gastric smooth muscle as well as in the airway of beta receptor overexpressing mice.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, in a study in which human PLB was expressed in transgenic mice, Kranias and co-workers concluded that lysine at position 27 makes PLB superinhibitory, inducing heart failure and cardiac remodeling in transgenic mice (38,39). Because of these effects observed in mice, novel functions for PLB in human myocardium were proposed (38,39). However, in the present study, we determined that human PLB (with Lys 27 ) inhibits SERCA2a activity to the same extent as canine PLB, which has Asn 27 .…”
Section: Mechanism Of Plb Inhibition In Sr Vesicles-it Is Largelymentioning
confidence: 99%
“…These findings suggest that compensatory hypertrophy is unlikely to be the cause of HCM induced by mutation of sarcomeric genes ( Ashrafian et al, 2011 ). PLN regulates sarcoplasmic reticulum Ca 2+ cycling in the heart through inhibition of ATPase sarcoplasmic/endoplasmic reticulum Ca 2+ transporting 2 (ATP2A2) ( Wang et al, 2011 ). Mutation of PLN causing superinhibition of ATP2A2 can cause HCM ( Wang et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…PLN regulates sarcoplasmic reticulum Ca 2+ cycling in the heart through inhibition of ATPase sarcoplasmic/endoplasmic reticulum Ca 2+ transporting 2 (ATP2A2) ( Wang et al, 2011 ). Mutation of PLN causing superinhibition of ATP2A2 can cause HCM ( Wang et al, 2011 ). Haploinsufficiency of ATP2A2 can also cause HCM, possibly through mitochondrial dysfunction ( Prasad et al, 2015 ), suggesting that mutation of PLN causing HCM may impair mitochondrial function.…”
Section: Introductionmentioning
confidence: 99%